Division of Labor in the Interpretation of Declaratives and Interrogatives. (20th January 2017) - Farkas, Donka F.; Roelofsen, Floris
Abstract: This article presents an account of the semantic content and conventional discourse effects of a range of sentence types in English, namely falling declaratives, polar interrogatives and certain kinds of rising declaratives and tag interrogatives. The account aims to divide the labor between compositional semantics and conventions of use in a principled way. We argue that falling declaratives and polar interrogatives are unmarked sentence types. On our account, differences in their conventional discourse effects follow from independently motivated semantic differences combined with a single convention of use, which applies uniformly to both sentence types. As a result, the Fregean 'illocutionary force operators' Assertion and Question become unnecessary. In contrast, we argue that rising declaratives and tag interrogatives are marked sentence types. On our account, their conventional discourse effects consist of the effects that are dictated by the basic convention of use that is common to all sentence types considered here, augmented with special effects that are systematically connected to their formal properties. Thus, a central feature of our approach is that it maintains a parallelism between unmarked and marked sentence types on the one hand, and basic and complex discourse effects on the other.